EFFORTS TO INCREASE THE MATHEMATICAL UNDERSTANDING ABILITY OF CLASS V STUDENTS IN SDN 3 BATUJAJAR IN THE SOLID NUMBERS MATERIALS USING CONTRUCTIVISM APPROACHES - Layla Saadah (IKIP Siliwangi, 2020)
The method in this study is the Classroom Action Research (CAR) method. PTK consists of four stages, namely planning, action, observation and reflection. PTK is carried out through 3 cycles of 6 meetings. Learning instruments consist of questionnaires, observation sheets of student activities, interview sheets, Student Worksheets (LKS) and evaluation sheets. The result of the implementation of PTK is an increase in mathematical comprehension and teacher and student activities from the first cycle to the third cycle. Teacher activities are more increasing than learning as usual, with the constructivism approach applied by the teacher acting as a facilitator, motivator and mediator for students. The increase in the ability of mathematical understanding and student activity is indicated by changes in scores and changes in scores of students who reach the KKM from the first cycle to the third cycle in a row namely 48.6%, 64.9% and 81.1%.